Republic of Mozambique : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This Joint Staff Advisory Note (JSAN) of the Poverty Reduction Strategy Paper (PARPA) for the Republic of Mozambique highlights the poverty situation and macroeconomic and fiscal frameworks. The strategy to consolidate macroeconomic stability and accelerate the second wave of reforms in PARPA II should facilitate sustained broad-based growth and poverty reduction. A good investment climate is essential for the development of the private sector, thereby fostering broad-based growth and employment creation. There is a need to develop systems for a timely delivery and improved dissemination of key results to the public.